Is action research coming of age? – The value of a history action research project in professional teacher development (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The new B.Ed curriculum at the University of Kwazulu-Natal proposes the inclusion of a compulsory action research module to provide professional skillsthat teachers are expected to demonstrate. The Norms and Standards Policy for Educators requires teachers to be transformative. An appropriate educationalcomponent would therefore be required to fulfil this need. By acknowledging the potential that action research offers a transformational teaching model, this paper deals with a pedagogical journey from a product-oriented to a process-oriented teacher. Action research does not necessarily change the teacher but it sensitises the teacher to alternative, more democratic practices and a critically reflective disposition. In this paper a method of “self-reflexive historiography” is used that involves reflecting retrospectively on professional development and identifying valuable lessons for the present. The context of the transformational experiences was an action research history teaching project conducted for a M.Ed degree (Davids, 1991). The research question that informs this article is: what are some of the lasting influences of an action research project on a teacher’s pedagogical comportment and what lessons were learnt that are relevant to teacher education today? Based on this case study, recommendations are made for the use of action research as pedagogy for professional practice in teacher education and in-service teacher initiatives.
Keywords: Norms and Standards; Action research; Transformational teaching; Professional development; Critical thinking; Teachers; Education